Analysis of droughttolerant maize adoption and its effect on food security among farmers in the Sudan Savanna of Northeastern Nigeria - Idrisa, Y.L.; Abdoulaye, Tahirou; Mohammed, S.T.; Ibrahim, A.A. (2014)
This article examined the factors influencing the adoption of the drought-tolerant Maize(DT) varieties and their effect on food security among farmers in the Sudan Savannaagro-ecological zone of northeastern Nigeria. Data for the study were collected from 200farmers who were selected through a multi-stage sampling procedure. Factors influencingthe adoption of DT maize varieties were determined through the use of censoredregression (the Tobit model) while the effect of adoption of DT maize on food security wasdetermined through the use of the chi-square test. The results from the chi-square testwere further converted to a contingency coefficient in order to obtain the extent of theassociation between the adoption of DT maize and food security. The study revealed thatincome (? ? 0.01) and access to extension services (? ? 0.01) were significant ininfluencing the adoption of DT maize among farmers. The study also found a strong association (?2 – cal = 15.53; ?2 – tab = 13.28) between the adoption of DT maize andfood security among farmers in the Sudan Savanna agro-ecological zone of northeasternNigeria with a contingency coefficient of 0.25. The study thus concluded that maizefarmers in the Sudan Savanna agro-ecological zone of northeastern Nigeria are generallysmall-scale farmers that produce for subsistence. It was also concluded that the adoptionof DT maize significantly reduced the level of food insecurity among farmers in the SudanSavanna agro-ecological zone of northeastern Nigeria. It was therefore recommendedthat farmers should be linked to source of market for their produce in order to boost theirincome and that extension services should be strengthened so as to give farmers accessto improved technologies.